Diode Laser - A Novel Therapeutic Approach in the Treatment of Chronic Periodontitis in Type 2 Diabetes Mellitus Patients: A Prospective Randomized Controlled Clinical Trial - Chandra, Sourav; Shashikumar, Pratibha (Journal of Lasers in Medical Sciences, 2018)
Introduction: Maturity-onset diabetes mellitus affecting the elderly population is marked by insulin resistance and decreased insulin production. The relationship between periodontitis and diabetes is bidirectional. Type 2 diabetic patients are more prone to chronic periodontitis (CP) and severe periodontitis affects the glycemic control in such patients. Recently, dental diode laser has become an effective tool in controlling CP. To date, very few studies have been conducted to check the efficacy of diode laser in control of periodontal destruction in type 2 diabetes mellitus (DM2) patients. Hence, the need of the study was to evaluate whether diode laser helps improvement of periodontal outcome and reduction in anaerobic bacteria in elderly diabetic patients with CP. Methods: Forty DM2 patients with CP were randomized into group A (control): scaling and root planing (SRP) only and group B (test): SRP followed by soft tissue dental diode laser (808 nm) application. Four patients (2 in each group) were lost during follow up. Clinical parameters, plaque samples and glycated hemoglobin levels were evaluated at both baseline and 90 days post-treatment. Results: Improvement in clinical, microbiological and glycemic parameters were noted in the group that received SRP as well as SRP + LANAP (laser-assisted new attachment procedure). The reductions in clinical parameters were statistically significant after 3 months (P < 0.001). The microbial analysis of plaque samples for Aggregatibacter actinomycetemcomitans (Aa) and Porphyromonas gingivalis (Pg) decreased significantly after 3 months in group B than in group A. Glycated hemoglobin level (HbA1c) decreased significantly after 90 days in both the groups (P < 0.001) with more reduction in the SRP+LANAP group (6.49%) in comparison to SRP alone (16.25% vs. 9.76%). However, on the intergroup comparison, the difference in HbA1c reduction was nonsignificant. Conclusion: Laser as an adjunct to SRP is an effective procedure for improving clinical and microbiological parameters in maturity onset diabetes mellitus patients with CP. Also, there was a better improvement in glycemic control in the test group compared to control group after 3 months. Hence, medically compromised patients like DM2 with CP with delayed wound healing can effectively be treated by laser as an adjunct to nonsurgical periodontal therapy for better results.